Pragmatics of accents - Planchenault, Gaëlle; Poljak, Livia (Pragmatics & beyond ;, 2021)
"What impact do accents have on our lives as we interact with one another? Are accents more than simple sets of phonetic features that allow us to differentiate from one dialect, variety or style, to the other? What power relationships are at work when we speak with what those around us perceive as an "accent"? In the 12 chapters of this volume, an international group of sociolinguists, applied linguists, anthropologists, and scholars in media studies, develop an innovative approach that we describe as the 'pragmatics of accents'. In this edition, we present a variety of languages and go beyond the traditional structural description of accents. From ideologies in national contexts, to L2 education, to accent discrimination in the media and the workplace, this volume embraces a new perspective that focuses on the use of accents as symbolic resources, and emphasizes the importance of context in the human experience of accents"--